A framework to support the development of quality simulation‐based learning programmes in speech–language pathology. Issue 2 (4th February 2020) - Hewat, Sally; Penman, Adriana; Davidson, Bronwyn; Baldac, Stacey; Howells, Simone; Walters, Joanne; Purcell, Alison; Cardell, Elizabeth; McCabe, Patricia; Caird, Emma; Ward, Elizabeth; Hill, Anne E.
Abstract: Background: Simulation‐based learning provides students with a safe learning environment, guaranteed exposure to specific clinical scenarios and patients, time for reflection and repetition of tasks, and an opportunity to receive feedback from multiple sources. Research including studies specific to allied health training programmes have demonstrated that simulation‐based learning also helps increase learners' confidence and reduces anxiety related to clinical environments, activities and skills. Such evidence, together with increasing challenges in provision of workplace clinical education, has supported an expansion of integrating simulation‐based learning into university curricula. Aims: To provide detailed information about the processes and considerations involved in the development of a simulation‐based learning programme for speech–language pathology. Methods & Procedures: Through reflection on the development process of a 5‐day simulation‐based learning programme, and in light of existing research in simulation, this paper outlines the important steps and considerations required for the development of a simulation‐based learning programme to support student competency development in adult speech pathology range of practice areas. Main Contribution: A proposed framework for the development of future simulation‐based learning programmes in speech–language pathology. Conclusions & Implications: The framework can be applied to simulation‐based learning for university programmes and/or workplace training in speech–language pathology and across several other health disciplines.